Factors Determining The Adoption of E-Procurement in Developing Countries: A Systematic Literature Review - Zulkarnain Zulkarnain; Iskandar Muda; Sambas Ade Kesuma (CV. Ridwan Publisher, 2023)
Technology is present to have an impact on business processes, E-Procurement is one form of this technological development. E-Procurement is a transaction for the procurement of goods and services by using internet services as a connecting tool in the transaction process. This research investigates the determinants of adopting e-procurement in several developing countries. This study reinforces the results of previous research on the determinants of E-Procurement adoption presented in the form of a systematic literature review (SLR). To evaluate and understand the patterns or themes of the selected documents, a systematic literature review is then carried out. In this study, 157 documents from various countries were published in peer-reviewed journals from 2000-2022 which were systematically reviewed. The results of the study reveal that in general the determinants of an entity in adopting E-Procurement are politics, socio-economic, demographic, geographical, government regulations, supplier participation and intentions, external organizational pressure, internal organizational support, network connectivity/integration, increased task or convenience in work, organizational culture, perception of resources, company size, electronic systems for processing orders and invoicing, organizational factors, readiness factors, supply factors, strategic factors, policy factors, innovation factors (Trust, Excellence/ benefits and image) moderating factors (uncertainty), Current Problems, Facilitators, inhibitors, potential benefits, Quality of Information (Online Information, Purchasing Procedures) and Quality of Logistics Fulfillment (accuracy of orders fulfilled, timely orders fulfilled).